Encoding Mie, plasmonic, and diffractive structural colors in the same pixel - Kim Youngji; Hyun Jerome K. (Nanophotonics)
We present a 1D reflective multi-level structural color design that incorporates Mie, plasmonic, and diffractive mechanisms in the same pixel. Comprised of a metallodielectric grating made of TiOx nanowires sandwiched between Ag thin film and Ag substrate, the design can exhibit either a Mie resonance or a localized plasmonic resonance depending on the polarization of incident light, resulting in dramatically different color states. Due to the periodicity, the grating also diffracts light, providing an additional color state. Since diffraction can be turned on or off by the degree of coherence of the incoming light, both Mie and plasmonic colors can be modulated using objective lenses with different numerical apertures. Exploiting the different color generating modes, we encode four layers of information in a pixel array, where each layer is unveiled using a different combination of excitation and imaging settings. These results introduce new possibilities for data encryption, anticounterfeiting, and data storage.